Urgensitas Pendidikan Islam Vis A Vis Pendidikan Barat Analisis Tantangan dan Harapan Perspektif Muhammad Iqbal - Moh Faizin; Annisa Aszhari; Aisyah Romadhona Amini; Nabila Grresita A.P.P (Lembaga Penelitian, Penerbitan dan Pengabdian (LP3M) IAI Al-Urwatul Wutsqo Jombang, 2023)
This article seeks to understand and explain the importance of Islamic education in comparison to Western education through a detailed examination of the challenges and expectations as seen through the eyes of Muhammad Iqbal. The research method employs a review of the literature to identify previous sources of relevant articles and journals. In this article, the author adopts the viewpoint of Muhammad Iqbal, a modern Islamic philosopher, writer, and reformer, to examine the benefits and drawbacks of Islamic and Western education. The discussion revealed that there is a significant difference between Islamic education and Western education, particularly in terms of scope and source material used. According to Muhammad Iqbal, Western education produces people with general science intelligence, whereas Islamic education produces people with good character and behavior. A good education must strike a balance between physical and spiritual aspects. Education's goal is to prepare men for life. Islamic education should be taught from childhood to adulthood so that the education provided covers a wide range of scientific topics. In the West, empirical aspects of real-life experience place a greater emphasis on educational resources. Whereas in Islamic education, the source of the value of knowledge comes directly from the creator of the universe rather than from the creation of experts or the elite of society. Because education is an investment in a better future; therefore, the educational process must run smoothly.